Desenvolvimento de rotina em python para o download automatizado de imagens gratuitas do satélite sentinel-2 - Stromm, Kamila Cassol (2022)
One of the main challenges for concessionaires has been the fight against non-technical energy losses. These losses are caused by fraud, theft, and defects in measuring equipment, and it has generated huge financial costs for companies. Therefore, distributors have intensified and improved the use of new technologies and methodologies to help identify these losses. In this context, the present work aims to develop an innovative methodology and computational platform for the automated download of satellite images, applied in irrigation areas. These images will be available later for monitoring meteorological variables and reference values for electricity consumption for each type of cultivar (rice, coffee, sugar cane...). The programming language used was Python and the satellite chosen for the process of downloading the images was Sentinel-2, because the images are free and it has a temporal resolution of only 5 days. The results obtained with the automation were satisfactory, since the time required by the researcher was considerably reduced compared to the collection of an image performed manually for each new study.